DESAIN SMART TOURISM UNTUK MERESPON KEMAMPUAN LITERASI DIGITAL WISATAWAN DI KECAMATAN TRAWAS, KABUPATEN MOJOKERTO, JAWA TIMUR - Parung, Joniarto; Gunawan; Pah, Nemuel Daniel; Arlianto, Jerry AgusJerry Agus Arlianto; Hapsari, Indri; Novawanda, Olyvia (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
This paper aims to design a smart tourism model and implement smart tourism to support the competitiveness of tourist destinations in the Trawas sub-district, Mojokerto Regency. A literature review on smart tourism is conducted as part of the introduction to understand why this design is needed. The design method uses the concept of exploratory design. The design results are applied as a virtual tour in the Trawas sub-district to benefit the community with digital devices (smartphones, laptops, PCs, etc.), virtual reality, and virtual tours to tourist destinations in the Trawas sub-district. This design still focuses on providing digital information to stakeholders that can be integrated with the roles of stakeholders in the tourism business. The result of the community service activity is the Smart Trawas application, which can be downloaded through the Play Store or App Store. This application will provide information in the form of videos, oral narration, and written about tourist destinations if users scan the QR code on the photo of the tourist destination. The photos are in 13 Trawas sub-district offices and at the Ubaya Training Center Trawas. Another result of community service is the availability of virtual tour links distributed by sub-district offices and related agencies in Mojokerto regency. --- Makalah ini bertujuan untuk merancang model smart tourism dan merealisasikan smart tourism untuk mendukung daya saing destinasi wisata di kecamatan Trawas, kabupaten Mojokerto. Tinjauan literatur tentang smart tourism dilakukan sebagai bagian dari pengantar untuk mengetahui mengapa diperlukan perancangan ini. Metode perancangan menggunakan konsep exloratory design. Hasil rancangan diaplikasikan dalam bentuk virtual tour di kecamatan Trawas untuk kepentingan masyarakat yang memiliki perangkat digital (handphone, laptop, PC komputer, dll), virtual reality dan virtual tour ke destinasi wisata kecamatan Trawas. Disain ini masih fokus untuk pemberian informasi secara digital kepada pemangku kepentingan yang siap diintegrasikan dengan peran pemangku kepentingan di bisnis wisata. Hasil kegiatan pengabdian adalah aplikasi Smart Trawas yang dapat diunduh melalui Playstore atau Appstore. Aplikasi ini akan memberi informasi dalam bentuk video, narasi lisan dan tulisan tentang destinasi wisata jika pengguna memindai QR code yang ada di foto destinasi wisata. Foto tersebut berada di 13 kantor desa di Kecamatan Trawas dan di Integrated Outdoor Campus (IOC) Ubaya. Hasil pengabdian yang lain adalah adanya link virtual tour yang telah disebarkan oleh kantor camat dan dinas terkait di Kabupaten Mojokerto.